PENERAPAN PORTOFOLIO INVESTASI ASET PROGAM DANA PENSIUN PADA OPTIMALISASI EXPECTED RETURN - Dwi Jaya Kirana (Universitas Pakuan, 2019)
This study aims to examine the implementation of pension fund asset allocation to equity, debt securities, time deposits, real estate, and others in determining expected returns. The samples used in this study are all listed companies that disclose the allocation of pension fund assets in 2016 -2018. The total sample is 93 companies. The analysis of this study uses multiple regression and statistical analysis of the Financial Services Authority (OJK). The results of the study show that all the variables of the allocation of pension fund assets have a significant effect on an expected return unless the other variables OTHER have a significant negative effect on expected return. The allocation of the defined benefit program assets and the defined contribution of the employer pension fund (DPPK) tend to be higher in equity and debt than the defined contribution assets of the Financial Institution Pension Fund (DPLK) more to deposits with fixed yields. Keywords : pension fund asset, allocation, expected return